2020
DOI: 10.36692/v12n3-33
|View full text |Cite
|
Sign up to set email alerts
|

Population Knowledge About Preventive Measures Against Sars-Cov-2 (Covid-19) in Northern Paraná – Brazil

Abstract: SARS-CoV2 has characteristics that are still unknown and therefore untreated. This disease demands efficient biosafety practices for professionals and the population considering the high infectivity rate of these viruses. The objective of this work was to evaluate the knowledge of the population of Northern Paraná - Brazil about the methods indicated for the prevention and reduction of the risk of infections in the midst of the COVID-19 pandemic. A field research was carried out in the form of a cross-sectiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 17 publications
1
1
0
Order By: Relevance
“…The biosafety assessed in this study, as reported in others in the literature 15,16 , confirmed that the entire sample uses some type of facial protection, either through disposable or tissue masks. Arruda et al 16 conducted a questionnaire among health students from a public university in Brazil and also reported that the entire sample used a mask for protection.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…The biosafety assessed in this study, as reported in others in the literature 15,16 , confirmed that the entire sample uses some type of facial protection, either through disposable or tissue masks. Arruda et al 16 conducted a questionnaire among health students from a public university in Brazil and also reported that the entire sample used a mask for protection.…”
Section: Discussionsupporting
confidence: 85%
“…Arruda et al 16 conducted a questionnaire among health students from a public university in Brazil and also reported that the entire sample used a mask for protection. Erthal et al 15 conducted a study that the sample was composed of health professionals and non-professionals in the area; in its results it was also verified the satisfactory use of the mask by the evaluated population.…”
Section: Discussionmentioning
confidence: 90%